Financial Performance of Banking in Indonesia: A Comparison Before and During the Covid-19 Pandemic - Nurdiniah, Dade; Pangestu, Yusuf (International Journal of Economics and Financial Issues, 2024)
This research aims to examine the financial performance of the banking sector in Indonesia both before and during the pandemic. In the course of this investigation, financial performance was evaluated using several factors namely Loan to deposit ratio (LDR), non-performing loan (NPL), return on assets (ROA), as well as operating expenses and operating income (BOPO). Furthermore, the data used comprised information on the banking financial conditions before (2018-2019) and during the pandemic-affected periods (2020-2021). Purposive sampling was used for sample selection and the analytical methodology adopted comprised the Wilcoxon signed rank test and paired samples t-test analysis. It is also crucial to establish that the present research utilized statistical computations conducted via the Statistical Package for the Social Sciences (SPSS) application, with a significance level of 5%. The obtained results showed that no significant difference was identified between LDR and BOPO both before and during the pandemic. However, a substantial difference was identified between NPL and ROA over the two examined periods.